Memahami Kebahagiaan Hidup Perkawinan dalam Terang Etika Eudaimonia Aristoteles dan Korelasinya dengan Pandangan Gereja Katolik - Lena, Damasus Frederiko; Mbukut, Antonius (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2024)
This article aims to (1) describe marriage and Aristotle's concept of eudaimonia. (2) describe the ideal model of happiness in married life amidst the increasing incidence of divorce. The ideal model of happiness in married life is examined from the perspective of Aristotle's eudaimonia ethics. (3) shows the correlation between Aristotle's understanding of happiness and the Catholic church's view of married life. The method used is a qualitative method. The author searches for and collects various related literature and proposes Aristotle's ideal concept of eudaimonia as an ideal model of happiness in married life by showing correlation with the views of the Catholic Church. This article shows the attitudes and actions that husband and wife must take to strengthen the marriage bond that has been vowed. The concrete attitude and action that needs to be taken is to try to know what happiness is and carry out typical actions while maintaining friendly relations within the marriage bond.